Traditional periodization versus optimum training load applied to soccer players: Effects on neuromuscular abilities - Loturco, I.; Nakamura, F. Y.; Kobal, R.; Gil, S.; Pivetti, B.; Pereira, L. A.; Roschel, H. (International Journal of Sports Medicine, 2016)
It is unknown whether traditional periodization of strength-power training involving accumulation, transformation and realization blocks is superior to other simpler and more practical training schemes. The purpose of this study was thus to investigate changes in strength/power/speed characteristics of elite soccer players in response to either classic strength-power periodization (TSP) or optimum power load (OPL). 23 professional soccer players were randomly assigned to TSP or OPL for 6 weeks in-season regular training (3 times per week). TSP involved half squats or jump squats, depending on the respective training block, while OPL involved only jump squats at the optimum power load. Results revealed that both groups presented similar significant (P<0.05) improvements in squat one repetition maximum, squat and countermovement jump heights and change of direction speed. In addition, although both groups reported significant increases in sprinting speed (P<0.05); delta change scores demonstrated a superior effect of OPL to improve 10- and 20-m speed. Similarly, OPL presented greater delta change in mean propulsive power in the jump squat. Therefore, training continuously at the optimum power zone resulted in superior performance improvements compared to training under classic strength-power periodization.